The wetting and the adhesion behavior of different types of polymers on air side and tin side of float glasses - Akdemir Kutluğ, Merve. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
In this study, the wettability and the adhesion behavior of different types of poymers on air side and tin side of float glasses were investigated and compared. First glass samples and coating materials were prepared for the coating process. Float glasses in 2 mm, in 4 mm and in 6 mm thickness and 10*10 cm dimensions were used. The glass samples were supplied from Trakya Glass San. A.Ş. Trakya Plant, were cleaned with acidic and basic cleaning agents in a dishwasher. Contact angle measurements of air side and tin side were taken with water to see the difference in wettability of both surfaces. Results of contact angle meaurements showed that the tin side of glass is more hyrophobic than the air side of the glass. Several polymers such as ethylene-acyrilic acid copolymer, etylene-maleic anhydride copolymer, polyvinly butyral, ionomer of ethylene acid copolymer, epoxy resin were prepared. The polymers were applied as water based emulsions or melts or soluitons in various solvents. Liquid molding resins were applied as liquids. The tin side of the glass samples was detected by using a UV tin side detector. Coating materials were applied on both the air and the tin side of glasses under specific conditions (temperature and time).. Adhesion tests were done by using Defelsko Positest AT-A Automatic Adhesion Tester. The adhesion test results were examined to characterize and observe the adhesion strength of different type of polymers on air side and tin side of float glasses. The best results were obtained with the samples when the polymers was applied as solutions ans with liquid molding resins because these liquid samples can fill all the holes or cavities on the glass surface and the glass is completely coated with the materials. When the solutions and liquid molding resins were applied on the tin side of the glass, the adhesive force was higher than the air side of the glass.
Keywords: Polymers.